Experimental investigation on the soil sorption properties and hydrophobicity of polymethoxylated, polyhydroxylated diphenyl ethers and methoxylated-, hydroxylated-polychlorinated diphenyl ethers. (September 2015) - Zhang, Xuesheng; Zeng, Xiaolan; Qin, Li; Qu, Ruijuan; Shi, Jiaqi; Wei, Zhongbo; Yang, Shaogui; Wang, Zunyao
Highlights: Fifty-nine DEs were synthesized and their log  K ow and log  K oc were determined. Sorption behaviors of five DEs on soil were well fitted the Freundlich model. The number of substituents significant influenced the log  K ow and log  K oc of DEs. Linear relationships were observed for the log  K ow and log  K oc of all studied DEs. Abstract: In the present study, twenty-six types of polymethoxylated diphenyl ethers (PMeODEs), twenty types of polyhydroxylated diphenyl ethers (PHODEs), seven types of methoxylated-polychlorinated diphenyl ethers (MeO-PCDEs) and seven types of hydroxylated-polychlorinated diphenyl ethers (HO-PCDEs) were synthesized. The log  K ow and log  K oc values of all of the synthesized compounds were then determined using HPLC. The soil sorption properties of five types of selected substituted diphenyl ethers (DEs) were investigated. Sorption behavior studies suggested that rapid sorption played a primary role in the sorption process of the selected DEs and their sorption isotherms were fitted the Freundlich logarithmic model. For PMeODEs and PHODEs, with the increase in the number of substituents, both log  K ow and log  K oc values exhibited linearly decreasing trends. Unlike PMeODEs and PHODEs, both log  K ow and log  K oc values of MeO/HO-PCDEs were decreased linearly with the increasing number of chlorine atoms. The reason maybe that both methoxy and hydroxyl are hydrophilic groups, whereas the chlorine atom is hydrophobic group. Linear relationships were observed for the log  K ow and log  K oc of all studied DEs. Moreover, the log  K ow of PMeODEs, PHODEs, MeO- and HO-PCDEs and their corresponding PCDEs showed good linearity.